A double‐blind randomised controlled trial on the effect of dehydroepiandrosterone on ovarian reserve markers, ovarian response and number of oocytes in anticipated normal ovarian responders. (10th December 2015) - Yeung, TWY; Chai, J; Li, RHW; Lee, VCY; Ho, PC; Ng, EHY
Abstract : Objective: To assess the effect of dehydroepiandrosterone (DHEA) on antral follicle count (AFC), ovarian response to a standard low dose of gonadotrophin stimulation and number of oocytes in anticipated normal responders undergoing in vitro fertilisation (IVF). Design: Randomised, double‐blind, placebo‐controlled study. Setting: Tertiary reproductive unit. Population: Seventy‐two subfertile women with AFC of 5–15 scheduled for IVF. Methods: Eligible women were randomised into the DHEA group ( n = 36), who received DHEA (GNC ®, 25 mg three times a day), or the placebo group ( n = 36), who received placebo, starting from 12 weeks before the scheduled IVF treatment according to a computer‐generated randomisation list. Monthly assessment of AFC, serum anti‐Mullerian hormone (AMH) and follicle‐stimulating hormone (FSH) levels, ovarian response to a standard dose of gonadotrophin stimulation at week 8 and the number of oocytes obtained were compared. Main outcome measures: The primary outcome was AFC after 12 weeks of DHEA or placebo. Results: DHEA for 12 weeks prior to IVF treatment in anticipated normal responders leads to significantly higher serum and follicular DHEA‐S and testosterone relative to placebo. However, no significant differences in AFC, AMH and FSH, ovarian response to standard‐dose ovarian stimulation and IVF cycle outcomes can be detected. Conclusion: No significant differences in AFC, ovarian response to a standard low dose of gonadotrophin stimulation and number of oocytes obtained were detected in anticipated normal responders receiving 12 weeks of DHEA prior to IVF treatment relative to placebo. Tweetable abstract: No difference in ovarian response markers in normal responders receiving 12 weeks of DHEA. Tweetable abstract: No difference in ovarian response markers in normal responders receiving 12 weeks of DHEA.